RANCANG BANGUN GAME MOBILE BERJENIS ROGUELIKE MENGGUNAKAN STRUKTUR CERITA BRANCHING NARRATIVE - Fadiel Mufassir; Caecilia Citra Lestari (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
In 2018 the total revenue from the digital game market has reached 137.9 billion USD with mobile being the largest segment of the digital gaming market. The games downloaded on Google Play have several categories, one of which is the role-playing category. That's where the opportunity to follow a trend appears by making an Android game that has the roguelike genre, which is a subgenre of role-playing games. Most games with the roguelike genre don’t have a story or it has a linear one with no control over the emotions of the player character, so this game will be made with a branching narrative story structure which allows players to choose the storyline to make it more interesting. A branching narrative offers the player with important choices; every choice offers a unique outcome to a certain scenario even though the number of outcomes in the story is limited. The survey shows that the branching narrative in the game can increase the curiosity of the player to the story in the game, increase the desire of players to play the game again, and that the branching narrative is strong enough to increase the desire of players to make an In-App Purchase.